![\frac{7}{24}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B24%7D%20)
÷
![\frac{35}{48}](https://tex.z-dn.net/?f=%20%5Cfrac%7B35%7D%7B48%7D%20)
Multiply
![\frac{7}{24}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B24%7D%20)
by the reciprocal of
![\frac{35}{48}](https://tex.z-dn.net/?f=%20%5Cfrac%7B35%7D%7B48%7D%20)
, which is
![\frac{48}{35}](https://tex.z-dn.net/?f=%20%5Cfrac%7B48%7D%7B35%7D%20)
=
![\frac{7}{24}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B24%7D%20)
×
![\frac{48}{35}](https://tex.z-dn.net/?f=%20%5Cfrac%7B48%7D%7B35%7D%20)
=
![\frac{336}{840}](https://tex.z-dn.net/?f=%20%5Cfrac%7B336%7D%7B840%7D%20)
We can simplify it further:
The greatest common factor here is
168
=
Thanks for the free points hope you find your awnser!
The answer is 1.25 meters.
hope it helps
can you choose mine as the brainliest answer
Answer:
Helena gave the answer as (7y²z + 6yz²- 5 - 3yz² + 2) which is equivalent to (7y²z + 3yz² - 3).
Step-by-step explanation:
Misha's group was asked to write an expression equivalent to
7y²z + 3yz² - 3
When Mr. Chen checked their answers, he found only one to be correct.
And she was Helena.
Helena gave the answer as (7y²z + 6yz²- 5 - 3yz² + 2) which is equivalent to (7y²z + 3yz² - 3).
Because, (7y²z + 6yz²- 5 - 3yz² + 2)
= 7y²z + (6yz² - 3yz²) - (5 - 2)
= 7y²z + 3yz² - 3 (Answer)
Answer:
the answer is :)
Step-by-step explanation: